Removal of copper from wastewater using rice polish (rice bran) - Singh K.K.; Hasan S.H. (My University, 2025)
Rice polish has boon successfully utilized for the removal of copper(II) from wastewater. The maximum removal of copper(II) has been found to be 97.5% at pH 8.0, initial CuII concentration 125 mg L-1 and temperature 20°C. The effect of different parameters are similar to that of cadmium sorption as described in the previous paper.